Cationized liposomal keto-mycolic acids isolated from Mycobacterium bovis bacillus Calmette-Guérin induce antitumor immunity in a syngeneic murine bladder cancer model. - Takayuki Yoshino; Jun Miyazaki; Takahiro Kojima; Shuya Kandori; Masanobu Shiga; Takashi Kawahara; Tomokazu Kimura; Takashi Naka; Hideyasu Kiyohara; Miyuki Watanabe; Sho Yamasaki; Hideyuki Akaza; et al. (PLoS ONE, 2019)
Intravesical therapy using Mycobacterium bovis bacillus Calmette-Guérin (BCG) is the most established cancer immunotherapy for bladder cancer. However, its underlying mechanisms are unknown. Mycolic acid (MA), the most abundant lipid of the BCG cell wall, is suspected to be one of the essential active components of this immunogenicity. Here, we developed cationic liposomes incorporating three subclasses (α, keto, and methoxy) of MA purified separately from BCG, using the dendron-bearing lipid D22. The cationic liposomes using D22 were efficiently taken up by the murine bladder cancer cell line MB49 in vitro, but the non-cationic liposomes were not. Lip-kMA, a cationic liposome containing keto-MA, presented strong antitumor activity in two murine syngeneic graft models using the murine bladder cancer cell lines MB49 and MBT-2 in comparison to both Lip-aMA and Lip-mMA, which contained α-MA and methoxy-MA, respectively. Interestingly, Lip-kMA(D12), which was made of D12 instead of D22, did not exhibit antitumor activity in the murine syngeneic graft model using MB49 cells, although it was successfully taken up by MB49 cells in vitro. Histologically, compared to the number of infiltrating CD4 lymphocytes, the number of CD8 lymphocytes was higher in the tumors treated with Lip-kMA. Antitumor effects of Lip-kMA were not observed in nude mice, whereas weak but significant effects were observed in beige mice with natural killer activity deficiency. Thus, a cationized liposome containing keto-MA derived from BCG induced in vivo antitumor immunity. These findings will provide new insights into lipid immunogenicity and the underlying mechanisms of BCG immunotherapy.